Tourist Attraction Strategies In The Destination Development Stage For Tourism Village Sustainability - Martina Amernia Manaraja; Haniek Listyorini (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
The development of tourism villages in Indonesia is expected to improve the village economy and be sustainable. In reality, not all tourist villages can be sustainable through all stages of destination development. Central Java Province Tourism Board has reported that only 4 per cent of villages survive through all of destination development stages. However, previous research has little attention in exploring strategies for change and innovation in tourist attractions at each stage of destination development. The purpose of this study is to explore the strategy of developing tourist attractions in the pioneer, developing and developed stages in Lerep Village Tourism. The method used is interactive qualitative research, data was collected by in-depth interviews with informants, observation and documentation. The results showed that Lerep Tourism Village focused on the development of natural and cultural tourism attractions in the pioneer stages, then in the developing stage it is strengthened by the presence of traditional culinary markets, as well as artificial tourism. In the developed stage, Lerep Tourism Village issued natural and cultural tourism packages with the concept of eco-educational tourism, strengthening agricultural tradition events and innovations in developing welcome dances for tourism.